Executive Committee Minutes 2011-11-03 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 10/20/11 approved. Correspondence received by the Chair. Report on Affordable Learning Solutions Initiative. Chair Report. CFA Report. Online Learning Policy referred to APC. Provost Report. MOU with Extended Education referred to APC. Disruptive Student Behavior Policy referred back to SAC. Priority Registration Policy revision approved for Senate agenda. Structure and Functions Report. Vice-President of SAEM Report. FSAC Report. EPC Report. Associated Students Report. Senate agenda approved.